2011
DOI: 10.1177/0021998310369596
|View full text |Cite
|
Sign up to set email alerts
|

Formulations for thermoplastic vulcanizates based on high density polyethylene, ethylene-propylene-diene monomer, and ground tyre rubber

Abstract: Thermoplastic vulcanizates (TPVs) are a specific group of the so called thermoplastic elastomers. The main characteristic is the existence of a crosslinked rubber phase obtained by dynamic vulcanization in the presence of the thermoplastic matrix. This article studies TPVs based on ground tyre rubber (GTR), high-density polyethylene, and ethylene propylene diene monomer rubber. Vulcanization is performed by a new peroxide developed to resist high temperatures and an standard one. The aim of this study is optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 23 publications
(27 reference statements)
0
39
1
Order By: Relevance
“…The literature has shown [41] that the lack of adhesion among phases in blends containing recycled elastomers is due to the large particles of elastomers, their superficial characteristics, and the structure of the cross-linkings, which hinder its absorption by molecules of the matrix as the use of only ground elastomer in blends makes the processing a difficult step [42], as observed in this work.…”
Section: Mechanical Propertiesmentioning
confidence: 57%
“…The literature has shown [41] that the lack of adhesion among phases in blends containing recycled elastomers is due to the large particles of elastomers, their superficial characteristics, and the structure of the cross-linkings, which hinder its absorption by molecules of the matrix as the use of only ground elastomer in blends makes the processing a difficult step [42], as observed in this work.…”
Section: Mechanical Propertiesmentioning
confidence: 57%
“…Also, studies utilizing GTR in thermoplastic elastomer observed the encapsulation of GTR by the rubber component and observed good mechanical properties (Naskar et al, 2001, Cañavate et al, 2011, Abou Zeid et al, 2008, Li et al, 2003b. In this study, low molecular weight liquid styrene butadiene rubber (LR) was used instead of a high molecular weight rubber, to improve the adhesion between RTR and EVA.…”
Section: Liqiud Rubber (Lr)mentioning
confidence: 99%
“…Rubber requires a long period to degrade naturally due to its cross-linked structure and the presence of stabilizers and other additives [1,2] , what consequently reduce its processability [3,4] . Many efforts have been made regarding the preparation and characterization of polymer blends containing GTR and various thermoplastics, as a recycling alternative [5,6] . The properties of these materials depend on the concentration of the recycled material, as well as the adhesion between the phases [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the adhesion between GTR and the polymer matrix is usually very weak as consequence of the three-dimensional structure generated by cross-linkings, in the case of blends in which the GTR is just ground [9][10][11] . Cañavate et al [6] report that the lack of adhesion between phases is a consequence of the large particle size of GTR, superficial characteristics and cross-linked structure, which hamper its adsorption by the thermoplastic matrix molecules. In the production of thermoplastic vulcanized blends (TPVs) containing recycled rubbers, the addition of a virgin rubber or the promotion of the rubber devulcanization (at least partial) are pre-requisites to obtain resultant good mechanical properties [12] .…”
Section: Introductionmentioning
confidence: 99%